2019
DOI: 10.1111/tbed.13439
|View full text |Cite|
|
Sign up to set email alerts
|

A molecular epidemiological investigation of PEDV in China: Characterization of co‐infection and genetic diversity of S1‐based genes

Abstract: Porcine epidemic diarrhoea virus (PEDV) is an emerging and re-emerging epizootic virus of swine that causes substantial economic losses to the pig industry in China and other countries. The variations in the virus, and its co-infections with other enteric viruses, have contributed to the poor control of PEDV infection. In the current study, a broad epidemiological investigation of PEDV was carried out in 22 provinces or municipalities of China during 2015-2018. The enteric viruses causing co-infection with PED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 39 publications
5
56
0
Order By: Relevance
“…As reported in our previous study, the PAstV-positive rate in diarrheic piglets was 16.39% (89/543), indicating wide distribution in China (9). In the present study, PAstV coinfection with 12 other porcine pathogens in diarrheic piglets was investigated.…”
Section: Coinfection Of Pastv With Multiple Porcine Pathogens In Diarsupporting
confidence: 58%
See 3 more Smart Citations
“…As reported in our previous study, the PAstV-positive rate in diarrheic piglets was 16.39% (89/543), indicating wide distribution in China (9). In the present study, PAstV coinfection with 12 other porcine pathogens in diarrheic piglets was investigated.…”
Section: Coinfection Of Pastv With Multiple Porcine Pathogens In Diarsupporting
confidence: 58%
“…Coinfections with more than one porcine pathogen are common and often more clinically severe (7,8). A previous surveillance study conducted by our group found a high percentage of coinfection among diarrheic piglets (9). PAstV, which has been identified as an important agent of diarrhea (10), and frequently presents as a coinfection with other porcine pathogens (3,5,6,9,11).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The PEDV variant strains have been detected in many provinces in China and have become one of the most economically important viral causes for diarrhea in piglets [36,37]. At present, piglet diarrhea, caused by PEDV infection, leads to huge losses in many pig farms [38].…”
Section: Discussionmentioning
confidence: 99%